The clinical characteristics, biochemical parameters and insulin response to oral glucose tolerance test (OGTT) in 25 transfusion dependent β-thalassemia (TDT) patients recently diagnosed with diabetes mellitus (DM): Diabetes mellitus in β-thalassemia - De Sanctis, Vincenzo; Soliman, Ashraf; Tzoulis, Ploutarchos; Daar, Shahina; Karimi, Mehran; Yassin, Mohamed A.; Pozzobon, Gabriella; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2022)
Background: Patients with transfusion dependent β-thalassemia (TDT) are at high risk for developing, over the time, a form of diabetes distinct from type 1 and type 2 diabetes, but with similarities to both. Aims of study: The aim of this study is to describe the clinical and laboratory data, and the insulin secretion and sensitivity, in TDT patients , recently diagnosed with diabetes mellitus (DM). Materials and Methods: The medical records of 25 TDT patients with DM, diagnosed by standardized oral glucose tolerance test (OGTT) and insulin secretion, were analysed; data were compared to TDT patients without diabetes and to a group of healthy subjects. Natural history of glucometabolic status before the diagnosis of DM was also reviewed.Results: On average, the TDT patients with DM were younger compared to TDT patients without diabetes. The mean age at diagnosis of  DM in female and male TDT patients was 24.0 ± 7.1 years and 31.9 ± 5.6 years, respectively (P: 0.007). Serum alanine aminotransferase values, basal insulin levels and prevalence of hypogonadism were consistently higher in TDT patients with DM compared to those without diabetes. Decreased insulin secretion and increased insulin resistance was observed in patients with DM. Conclusion: The natural history of glucometabolic status in TDT patients is characterized by a deterioration of glucose tolerance over time. Iron overload and liver dysfuction are the main factors responsible for glucose disturbances (GD) in TDT patients. The therapeutic approach must be individualized and followed by a multidisciplinary team.